Рассказы и сказки советских писателей - Марченко С. В. (Средне-Уральское книжное издательство, 1990)
Экземпляры: ф.6 (20201217) / Инвентарный номер: 59785 / Цена: 30.00 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: Р24 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6